Genomic Characterization and Functional Validation of Six cis-Regulatory Sequences in Medicinal Plant Andrographis paniculata - Xingbin Lv; Hua Yang; Yufang Hu; Qi Liang; Shuyun Tian; Lang Yang; Mingkun Huang; Ling Zhang; Yanqin Xu (Horticulturae)
Plant cis-regulatory sequences (CRSs) are essential for gene expression and transcriptional regulation in plants. With the rapid development of plant biotechnologies, such as transgenesis and gene editing tools, plant-derived CRSs have gradually replaced traditional CRSs, like the 35S promoter, to avoid some negative effects caused by exogenous DNA sequences. In this study, we provided a comprehensive analysis of the published genomic data of Andrographis paniculata and identified six candidate ApACRs. Based on the transient assays, two candidate CRSs (ApACR1 and ApACR2) demonstrated high transcriptional activities comparable to those of the 35S promoter in several plant species, in contrast to others with lower activities, suggesting their further potential applications in plant biotechnology and genetic engineering.